A More Competent, Warm, Feminine, and Human Leader: Perceptions and Effectiveness of Democratic Versus Authoritarian Political Leaders. Issue 1 (12th July 2021) - Sainz, Mario; Moreno-Bella, Eva; Torres-Vega, Laura C.
Nowadays, to the detriment of democratic leaders, the emergence of authoritarian leaders has drastically modified the political sphere. This project aims to shed light on this issue by analysing how the perceived effectiveness of democratic and authoritarian political leaders are shaped by the common dimensions of social perception, such as competence/warmth, masculinity/femininity, and human uniqueness/human nature. Accordingly, three experimental studies were conducted. In Study 1 ( n = 1001), we revealed that democratic leaders are perceived as more competent, warm, feminine and human. In Study 2 ( n = 548) and Study 3 ( n = 622), we investigated whether these dimensions of perception mediated the relationship between leaders and their perceived effectiveness. The results revealed that democratic leaders are perceived as effective in cooperative scenarios due to their competence, femininity, and human nature. Alternatively, democratic leaders are preferred in ambiguous contexts due to their competence and cognitive flexibility, that is, human nature. In contrast, authoritarian leaders are perceived as effective in competitive scenarios because of their masculinity. In Study 3, we manipulated the (in)stability of socio-economic contexts. The results revealed that democratic and authoritarian leaders are perceived as more competent, warm, human and more effective in socio-economic contexts that are stable compared with those that are unstable. The implications of the results regarding the emergence of authoritarian leaders are discussed.